RESEARCH OF THE ELECTRICAL CHARACTERISTICS OF FUEL ELEMENTS AS A POWER SOURCE FOR THE INNOVATIVE DEVELOPMENT OF ENVIRONMENTALLY SAFE TRANSPORT - ШВЕДЧИКОВА, І. О.; ПАНАСЮК, І. В.; СОЛОШИЧ, І. О.; МАЛИЙ, Я. С. (Technologies and Engineering, 2024)
Purpose. Development of methodological recommendations for conducting laboratory (practical) classes on the study of physical properties of fuel cells for use in the educational process of training applicants at various levels of higher education and in various educational programs. Methodology. It involves processing experimental data obtained during research and identifying regularities regarding the influence of such factors as the concentration and temperature of the ethanol solution on the energy characteristics of the Micro-DEFS type fuel cell. Findings. Methodical recommendations for performing practical (laboratory) works dedicated to studying the physical properties of ethanol fuel cells have been developed. Test results obtained during an experiment to determine the effect of ethanol concentration on the energy characteristics of an ethanol fuel cell are presented. It is shown that methodological recommendations have a universal character and are adapted to the capabilities and needs of applicants studying at different educational programs and levels of training: first (bachelor’s) and second (master’s). Originality. With the use of an experimental sample of Horizon FCJJ-22 Fuel Cell type Micro-DEFS, methodological recommendations of a research orientation have been developed for applicants studying in various educational programs, the structure of which includes consideration of theoretical issues, in particular familiarisation with chemical reactions at the electrodes of a fuel cell, as well as conducting experimental studies to determine the influence of several factors on the operating characteristics of the fuel cell. Practical value. The developed methodological recommendations for the study of the physical properties of ethanol fuel cells are intended for use during laboratory and/or practical classes with students of higher education who will study in various specialities and educational programs. The knowledge and skills acquired during such courses will become the basis for expanding the students’ knowledge about new technologies in the field of alternative energy.